(untitled) (Journal of Computational Mathematics, 2002)
For the first order nonstationary hyperbolic equation taking the piecewise linear discontinuous Galerkin solver, we prove that under the uniform rectangular partition, such a discontinuous solver, after postprocessing, can have two and a half approximative order which is half order higher than the optimal estimate by Lesaint and Raviart under the rectangular partition.